Pendampingan Komunikasi Pemasaran Berbasis Nilai FAST melalui Produksi Iklan Syariah untuk Penguatan Brand Awareness SMA Perjuangan Terpadu Depok - Velda Ardia; Robby Milana; Istisari Bulan Lageni; Sigit Surahman; Sofia Hasna; Ichwan Arifin (Jurnal Solusi Masyarakat (JSM), 2026)
Increasing competition among private schools requires effective marketing communication to strengthen institutional brand awareness. This community service program aimed to assist SMA Perjuangan Terpadu Depok in developing marketing communication based on FAST values (Siddiq, Amanah, Fathanah, and Tabligh) through the production of a Sharia advertising video. A participatory mentoring approach was implemented through four stages: needs assessment, communication strategy development, advertising production, and evaluation. The program resulted in a FAST based marketing communication mentoring model that integrated professional advertising practices with Islamic values. In addition to producing a Sharia advertising video, the program enhanced the school's understanding of communication planning, creative brief development, media planning, and digital promotion. Participants expressed positive responses and intended to use the video as a branding medium. The mentoring model offers a practical reference for Islamic educational institutions in developing ethical and sustainable marketing communication.